Volume 3: 18th International Conference on Advanced Vehicle Technologies; 13th International Conference on Design Education; 9t 2016
DOI: 10.1115/detc2016-59661
|View full text |Cite
|
Sign up to set email alerts
|

Significance, Prevalence and Implications for Bio-Inspired Design Courses in the Undergraduate Engineering Curriculum

Abstract: Engineers in the 21st century can no longer isolate themselves and must be prepared to work across disciplinary, cultural, political, and economic boundaries to meet challenges facing the US and the world. Recently, a greater emphasis is being placed on understanding social, economic and environmental impacts of engineered solutions. Undergraduate education must train students to not only solve engineering challenges that transcend disciplinary boundaries, but also communicate, transfer knowledge, and collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Based on the assessment results from student reflection responses and the student work products, these students demonstrated engagement in learning, an ability to recognize and formulate interrelationships across disciplinary boundaries, as well as bring innovation to the design solutions. The student responses from the reflection questions and consideration of what the instructional resources were intended to foster led to the creation of a map of competencies for the 21 st century engineer that can be attained by teaching bio-inspired design to engineering students 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the assessment results from student reflection responses and the student work products, these students demonstrated engagement in learning, an ability to recognize and formulate interrelationships across disciplinary boundaries, as well as bring innovation to the design solutions. The student responses from the reflection questions and consideration of what the instructional resources were intended to foster led to the creation of a map of competencies for the 21 st century engineer that can be attained by teaching bio-inspired design to engineering students 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Search terms included 'teaching', 'training', 'education', 'course', 'class', 'BID', 'biomimicry', 'biomimetics', and combinations of the terms. As there are various overviews and analyses on teaching institutions and practices, for example, [40,57], the search was also based on the references sections in identified relevant publications.…”
Section: Topics Of Teaching Modulesmentioning
confidence: 99%
“…Attempts were made to explore the C-K theory based bioinspired design process model through the teaching -learning process in undergraduate bioinspired design engineering courses using qualitative analysis techniques. It was found that the C-K theory based bioinspired design process resulted in significant student learning and engagement [21][22][23].…”
Section: Introductionmentioning
confidence: 99%